A Prospective Comparative Analysis Regarding the Assessment of Oral Mucosal Disease Using a Validated Questionnaire to Improve the Teaching of Dental Students - Röschmann, Nico; Rau, Andrea; Kesting, Marco Rainer; Maier, Eva; Buchbender, Mayte (International Journal of Environmental Research and Public Health, 2022)
Structured examination and treatment are essential in medicine. For dental students, a structured approach to the assessment of oral mucosal lesions is missing thus far. To validate an approach, a structured questionnaire was compared with the habitually used free description of oral lesions (white lesions, ulcers, hyperplasia). Thirty-three dental students were divided into two groups (Group 1 (n = 17) used the free description; Group 2 (n = 16) used a guided questionnaire) to characterize mucosal lesions in patients and make a tentative diagnosis. Although no difference was found between the groups regarding the suspected diagnosis or the histopathological findings, there was a significant advantage of the structured questionnaire in all aspects of the description compared to the free description (p = 0.000018). Thus, a structured description is an important aspect in the evaluation of oral mucosal changes, and a guided questionnaire should be implemented in the study of dentistry.
CRIS-Team WoS Importer:2022-08-26

COVID-19 pandemic and its impact on dental education: digitalization - progress or regress? Example of an online hands-on course - Oetter, Nicolai; Möst, Tobias; Weber, Manuel; Buchbender, Mayte; Rohde, Maximilian; Foerster, Yannick; Bauerschmitz, Charlotte; Röschmann, Nico; Adler, Werner; Rau, Andrea; Meyerolbersleben, Marion; Kesting, Marco Rainer; et al. (BMC Medical Education, 2022)
BACKGROUND: Due to the SARS-CoV-2 pandemic and the accompanying contact restrictions, a new challenge arose for dental education. Despite the limited overall situation, it must be ensured that, in addition to theoretical content, practical skills in particular continue to be taught. Therefore, the aim of this study was to develop and implement an online hands-on course for dental students that ensures practical training, even during the pandemic. METHODS: The newly developed course was held from April 2020 to March 2021. A total of six groups (each consisting of approximately 40-50 students) took part in the course. The participating students were in their 3rd, 4th or 5th year of study. The course taught theoretical basics (via an online platform) and promoted the learning of practical/surgical techniques on models such as bananas, pork bellies, or chicken thighs with live demonstrations (via ZOOM) and interactive post-preparation by students at home (and in a rotating small group of 3-7 students on site). Student self-evaluation (at the beginning and end of the course) and course evaluation were performed using questionnaires. The learning success was analyzed (through self-evaluations) using Wilcoxon signed-rank tests (significance level alpha = 0.05). RESULTS: Concerning students´ self-evaluations, the theoretical knowledge, general surgical skills (such as surgical instrument handling), and specific surgical skills (such as performing a kite flap) improved during the course, with significant results (p < 0.001 for each). About 60% of the students rated the course overall as excellent (grades 9 or 10 on a Likert scale of 1 to 10). The technical implementation of the course was rated with a median of 9 (= very good, on a Likert scale of 1 to 10). 38.5% described the applicability of the skills learned for their later professional life as extremely good. CONCLUSIONS: The results of this work suggest that, within the limitations of this study, the introduced concept of an online hands-on course could be an appropriate form of teaching practical dental skills, even during a pandemic. Further research is needed in the field of digital education for dental students.
Created from Fastlane, Scopus look-up
Keywords: Asynchronous; Coronavirus; Dentistry; Digital; Education; Pandemic; Synchronous